The Effect of Coloring Art Therapy on Academic Anxiety of Midwifery Final Year Students: Pengaruh Terapi Seni Mewarnai Terhadap Kecemasan Akademik Mahasiswa Tingkat Akhir Jurusan Kebidanan - Afidayani, Khairunnisa; Khairani, Wittin; Laasara, Nurun (Caring : Jurnal Keperawatan, 2023)
Academic anxiety is an impulse of thoughts and inner feelings that contain tension and fear, which results in disruption of thought patterns, physical responses, and behavior as a result of pressure in academic situations. Academic anxiety felt by students can affect their achievement index. One of the therapies that can be used to reduce academic tension is coloring art therapy, which can reduce anxiety levels and improve individual coping mechanisms. Objective of this research to heal the effect of coloring art therapy on the academic anxiety of final-year students of the Department of Midwifery, Poltekkes, Ministry of Health, Yogyakarta. This research is a pre-experimental design with a one-group pre-post-test design. Sampling technique with purposive sampling The sample used was the final-year students of the Midwifery Department, totaling 76 respondents. Statistical test using the Wilcoxon signed rank test. This study showed that 11% of students experienced mild anxiety, 68% experienced moderate anxiety, and 21% experienced severe anxiety based on the results of the pre-test scores. After coloring art therapy using the media "Guidance Book: Coping with Art," based on the results of the post-test, as many as 50% of respondents experienced mild anxiety, 46% of students experienced moderate anxiety, and 4% experienced severe anxiety. Statistical test results show the value of Asymp. Sig (2-tailed) or p.value 0.000 (P  0.05). Coloring art therapy has an effect on academic anxiety in final-year students of the Midwifery Department of the Yogyakarta Ministry of Health Polytechnic.   Kecemasan akademik adalah dorongan pikiran, perasaan dalam diri yang berisikan ketegangan dan ketakutan yang mengakibatkan terganggunya pola pemikiran, respon fisik serta perilaku sebagai hasil tekanan dalam situasi akademis. Kecemasan akademik yang dirasakan mahasiswa dapat mempengaruhi indeks prestasi setiap mahasiswa. Salah satu terapi yang dapat digunakan untuk mengurangi kecemasan akademik adalah terapi seni mewarnai yang dapat menurunkan tingkat kecemasan dan meningkatkan mekanisme koping individu. Tujuan penelitian ini untuk diketahuinya pengaruh terapi seni mewarnai terhadap kecemasan akademik mahasiswa tingkat akhir Jurusan Kebidanan Poltekkes Kemenkes Yogyakarta. Penelitian ini merupakan penelitian pre-experimental designs dengan one-group pre-post test design. Teknik pengambilan sampel dengan purposive sampling. Sampel yang digunakan merupakan mahasiswa tingkat akhir Jurusan Kebidanan berjumlah 76 responden. Uji statistik menggunakan Wilcoxon signed ranks test.  Penelitian ini menunjukkan bahwa 11% mahasiswa mengalami kecemasan ringan, 68% mahasiswa yang mengalami kecemasan sedang dan 21% mahasiswa mengalami kecemasan berat dari hasil nilai pre-test. Setelah dilakukan terapi seni mewarnai menggunakan media “Guidance Book: Coping with Art” berdasarkan hasil post-test sebanyak 50% responden mengalami kecemasan ringan, 46% mahasiwa mengalami kecemasan sedang dan 4% mengalami kecemasan berat. Hasil uji statistik menunjukan nilai Asymp. Sig (2-tailed) atau p.value 0,000 (P < 0,05). Terapi seni mewarnai berpengaruh terhadap kecemasan akademik pada mahasiswa tingkat akhir Jurusan Kebidanan Poltekkes Kemenkes Yogyakarta.